Ecological distribution study of wild pistachios for selection of roostock - Behboodi B.S. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
The main origin of pistachio is the Iran plateau. There are pistachio forests in the west, east, south and centre of the country, and composed of three species: P. vera, P. atlantica and P. khinjuk. In this research work, we have tried to study the distribution of different species related to ecological factors in different parts of Iran. By contacting four different herbaria and visiting different parts of Iran, we collected specimens of pistachios. Also by using different geological and ecological maps, we tried to compose several new geo-ecological maps of the distribution of the pistachio in the country. We considered different factors, such as the minimum and maximum temperatures, the amount of rain, the climate and the height of the regions. Using this new information, we could select the wild species that are most resistant to harsh conditions, like dry weather and salinity, etc., in order to choose resistant rootstocks. These rootstocks will grow better and will live longer. This study suggests that P. khinjuk could be the best rootstock for most regions in Iran.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)